2014
DOI: 10.2528/pier13103101
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Target Recognition Using Feature Vector Fusion of Monostatic and Bistatic Radar

Abstract: Abstract-This paper proposes a fusion technique of feature vectors that improves the performance of radar target recognition. The proposed method utilizes more information than simple monostatic or bistatic (single receiver) algorithms by combining extracted feature vectors from multiple (two or three) receivers. In order to verify the performance of the proposed method, we use the calculated monostatic and bistatic RCS of three full-scale aircraft and the measured monotatic and bistatic RCS of four scalemodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Due to the massive recognition researches focusing on real HRRPs during past years [10][11][12][13][14][15][16], the discriminant process of HRRP's amplitudes is moderately reduced as that. Firstly, through the preprocessed method offered in [2], we obtain the training spaceĀ from the original space A. Secondly, with the help of LDA, we obtain the FPS U A from the training spaceĀ.…”
Section: The Recognition Of Hrrp's Amplitudesmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the massive recognition researches focusing on real HRRPs during past years [10][11][12][13][14][15][16], the discriminant process of HRRP's amplitudes is moderately reduced as that. Firstly, through the preprocessed method offered in [2], we obtain the training spaceĀ from the original space A. Secondly, with the help of LDA, we obtain the FPS U A from the training spaceĀ.…”
Section: The Recognition Of Hrrp's Amplitudesmentioning
confidence: 99%
“…Among several kinds of the windband radar target signatures, such as 2-D and 3-D radar target images [3], HRRP is a promising signature and more easy to be acquired in actual application, but it is highly sensitive to target-aspect, time-shift and amplitude-scale variations [4][5][6], so how to extract robust and effective feature from the raw signal becomes a key problem in HRRP-based radar automatic target recognition (RATR). During the past decade, many measured and simulated experimental results also confirmed that some physical structure information naturally contained in complex HRRPs, such as target size [7], scatterer distribution [8,9], amplitude fluctuation [10][11][12][13][14][15][16], is very beneficial to HRRP-based RATR, and accordingly, a number of statistical methods have been proposed for feature extraction and dimension reduction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The target classification experiment was then per-formed by fusing these feature vectors. Other fusion techniques are presented in [6,7].…”
Section: Introductionmentioning
confidence: 99%